2005
DOI: 10.1007/s00421-004-1300-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of peak $$\dot V{\text{O}}_2 $$ and maximal cardiac output assessed using thoracic bioimpedance in children

Abstract: The purpose of this study was to evaluate the reliability of a thoracic electrical bioimpedance based device (PhysioFlow) for the determination of cardiac output and stroke volume during exercise at peak oxygen uptake (peak VO(2) in children. The reliability of peak VO(2) is also reported. Eleven boys and nine girls aged 10-11 years completed a cycle ergometer test to voluntary exhaustion on three occasions each 1 week apart. Peak VO(2) was determined and cardiac output and stroke volume at peak VO(2) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 33 publications
(54 reference statements)
2
62
1
1
Order By: Relevance
“…The HR, RER and blood [lactate] criteria that are commonly applied for the acceptance of a _ VO 2 'max' both in adult and paediatric populations has recently been challenged (Barker et al 2009;Poole et al 2008b). Consequently, the peak _ VO 2 values reported here cannot be definitively stated to reflect a maximal effort and are presented for consideration within the limits of reliability reported for peak _ VO 2 determined using this traditional methodology (Welsman et al 2005).…”
Section: Peak Physiological Responsesmentioning
confidence: 92%
“…The HR, RER and blood [lactate] criteria that are commonly applied for the acceptance of a _ VO 2 'max' both in adult and paediatric populations has recently been challenged (Barker et al 2009;Poole et al 2008b). Consequently, the peak _ VO 2 values reported here cannot be definitively stated to reflect a maximal effort and are presented for consideration within the limits of reliability reported for peak _ VO 2 determined using this traditional methodology (Welsman et al 2005).…”
Section: Peak Physiological Responsesmentioning
confidence: 92%
“…The Physio Flow uses a high-frequency and low-amperage alternating electrical current via six electrodes. The Physio Flow has been found to be a valid and reliable estimate of cardiac output and stroke volume at rest and during moderate to high-intensity exercise in healthy normal weight (Charloux et al 2000;Palmieri et al 2006;Richard et al 2001;Tordi et al 2004;Welsman et al 2005), overweight (Richard et al 2001;Palmieri et al 2006), and obese (Palmieri et al 2006) participants. Richard et al (2001) evaluated the reproducibility and accuracy of the Physio Flow against the direct Fick method during an incremental exercise test from rest to maximal exercise in normal-weight and overweight participants.…”
Section: Cardiac Variables Measurementsmentioning
confidence: 99%
“…Test-retest reproducibility was reported as an intraclass correlation coefficient for stroke volume (0.77) and cardiac output (0.56). Welsman et al (2005) reported reliability of the Physio Flow during highintensity cycling exercise (comparing three trials). When three trials were analyzed together, error expressed as a coefficient of variation was 9.3% for cardiac output and 9.3% for stroke volume.…”
Section: Cardiac Variables Measurementsmentioning
confidence: 99%
“…Cardiac output ð _ QÞ was measured using a non invasive impedance cardiograph device, the PhysioFlow PF-05 (Manatec biomedical, Paris, France). The PhysioFlow concept and methodology have been recently validated at rest and at exercise (Charloux et al 2000) and during a maximal progressive exercise (Richard et al 2001;Welsman et al 2005). This bioimpedance method of _ Q determination uses changes in thoracic impedance during cardiac ejection to calculate stroke volume (SV).…”
Section: Blood Analysesmentioning
confidence: 99%